Design optimisation of shroud-augmented dual-rotor exhaust air energy recovery wind turbine generator using hybrid non-destructive evaluation approach - Yap, H. T.; Ong, Z. C.; Chong, W. T.; Kong, K. K.; Khoo, S. Y.; Z., Ismail; Abdul Ghaffar, Abdul Rahman (Elsevier Ltd, 2014)
An innovative system for recovering exhaust gas is created to recycle the energy from industry cooling tower waste. Two Vertical Axis Wind Turbines (VAWTs) with enclosure are positioned at a specific position at the outlet of cooling tower to harness the wind energy for electricity generation. From structural dynamics aspect, adding two VAWTs or dual-rotor with enclosure can contribute extra burden to the cooling tower. This has changed the dynamic characteristics of the cooling tower. Therefore, a hybrid non-destructive evaluation approach is proposed to investigate the dynamic behaviour and reliability of this new design. From this approach, it was found that the overall vibration of the cooling tower increased from 3mm/s to 26mm/s after the installation of the VAWTs with enclosure. The VAWTs are not operating at its optimum speed due to energy loss in vibration. The operating speed of VAWTs (i.e. 7.5Hz) was found close to one of the natural frequencies of VAWT (i.e. 7.0Hz). This indicates structural dynamic weakness which causes high vibration as recorded. Structural Dynamic Modification (SDM) is performed on the new design in the attempt to reduce the vibration at VAWTs and improve the reliability of VAWTs with enclosure in order to ensure optimum operation of VAWTs. The SDM is expected to shift the natural frequency away from the operating frequency with around 81% of reduction in vibration level which leads it to safe and unrestricted long-term operation. In addition, reducing vibration at VAWTs also recovers the energy loss of 419 Joules and subsequently maximises the efficiency of wind turbine.